Buku Digital untuk Pembelajaran di Era Society 5.0 - Muhammad Saifudin Zuhri; Tutut Chusniyah; Muslihati (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
In Society 5.0, technological developments are speedy and rapid. Human life is side by side with technological progress. Therefore, the use of technology in society is evenly distributed. Many conveniences are obtained using Android, including learning resources that add insight or reading material. This research is R&D with the ADDIE development model. The product of this research is a digital learning book sub-theme four, living in harmony in society. The purpose of this research and development is to produce a product that is valuable, effective, practical and attractive. Product test results resulted in media expert validation of 90%, while material validation was 86%. The results of the two validations are average in the excellent category. The results of the effectiveness test were obtained from student learning outcomes through evaluation questions with an average of 87 and a completeness percentage of 92.85%, and these results were included in the very effective and complete category. The results of the practicality test obtained a percentage of 95% of teachers and 96.72% of students included in the practical category. The results of the attractiveness test showed that the percentage of students was 96.52% which was included in the desirable category. Based on the explanation above, it shows that independent digital books as alternative teaching material in Society 5.0 are appropriate to use in the category of valid, effective, practical and interesting.